Investigating the psychology of green transportation via the green service profit chain. Issue 3 (June 2015) - Chen, S.-Y; Lu, C.-C.
<x content-type="archive" xml:space="preserve">Abstract</x> This work studies the effect of green satisfaction (GS), green word of mouth (GWOM), and green trust (GT) on green loyalty (GL) and the mediation effect of GWOM on green transportation (GTR). The objective of this research is to identify how to establish GL for GTR via the green service profit chain (GSPC) based on Heskett et al. (1994) and GT. This investigation applies structural equation modeling (SEM) to analyze the empirical results, and the findings indicate that GS and GT have positive influences on GL. On the other hand, it is verified that GS and GT positively affect GWOM, and GWOM also positively influences GL for users of YouBike. The overall influential effect of GS is higher than the overall effect of GT on GL (0·462>0·220). Therefore, GWOM has a mediation effect between GL, GT, and GS, and GS produces GWOM more powerfully than does GT. Finally, governmental institutions should strive to increase users' GS, GWOM, and GT to enhance their GL to YouBike.